2021
DOI: 10.1186/s41983-020-00265-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors for cerebral palsy

Abstract: Background Cerebral palsy (CP) has been identified as one of the most important and common causes of childhood disabilities worldwide and is often accompanied by multiple comorbidities. CP is defined as a group of disorders of the development of movement and posture, causing activity limitation that are attributed to non-progressive disturbances that occurred in the developing fetal or infant brain. The objective of our study was to describe main clinical pattern and motor impairments of our pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 54 publications
4
16
0
Order By: Relevance
“…According to this study, preconception is defined as the health conditions of the mother before conception, prenatal is defined as the period of gestation, perinatal is during delivery, and postnatal is after delivery [ 2 ]. A study in 2021 also found that the risk factors for cerebral palsy were 21%, 30.5%, 17.1%, and 31.4% when grouped under prenatal, perinatal, postnatal, and unidentified categories [ 9 ]. Preconception risk factors include the mother's systemic illness, substance abuse, maternal undernutrition, swallowing harmful substances, fertility issues, and previous spontaneous termination of pregnancy [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to this study, preconception is defined as the health conditions of the mother before conception, prenatal is defined as the period of gestation, perinatal is during delivery, and postnatal is after delivery [ 2 ]. A study in 2021 also found that the risk factors for cerebral palsy were 21%, 30.5%, 17.1%, and 31.4% when grouped under prenatal, perinatal, postnatal, and unidentified categories [ 9 ]. Preconception risk factors include the mother's systemic illness, substance abuse, maternal undernutrition, swallowing harmful substances, fertility issues, and previous spontaneous termination of pregnancy [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…This implies that infection can exert direct neurological injury by decreasing the threshold of neonatal apoptosis induced by hypoxia or indirectly by a non-hypoxia pathway. Fetal inflammatory process and hypoxia seem to work synergistically, resulting in abnormal rapid fetal tracing [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conditions during and after birth, hypoxic-ischemic encephalopathy (28.5%), infections, especially of the nervous system (16.3%), hyperbilirubinemia (12.7%), cerebrovascular disorders (8.8%), meconium aspiration (6.2%), and intracranial hemorrhage (8.7%) contributed to the incidence of cerebral palsy in children. 3 Impaired motor function is the main symptom of cerebral palsy, followed by other symptoms such as sensory, cognitive, communication, behavioral disturbances, epilepsy, and disorders of the muscles and bones. 4 The nutritional status of children with cerebral palsy is a very serious problem that needs to be treated early.…”
Section: Introductionmentioning
confidence: 99%